In vivo CEST Imaging of Creatine (CrCEST) in Skeletal Muscle at 3T - Kogan, Feliks (2013)
PURPOSE: To characterize the chemical exchange saturation transfer (CEST) based technique to measure free creatine (Cr), a key component of muscle energy metabolism, distribution in skeletal muscle with high spatial resolution before and after exercise at 3T. METHODS: CrCEST saturation parameters were empirically optimized for 3T. CEST, T(2), magnetization transfer ratio (MTR) and (31)P magnetic resonance spectroscopy (MRS) acquisitions of the lower leg were performed before and after mild plantar flexion exercise on a 3T whole-body MR scanner on 6 healthy volunteers. RESULTS: The feasibility of imaging Cr changes in skeletal muscle following plantar flexion exercise using CrCEST was demonstrated at 3T. This technique exhibited good spatial resolution and was able to differentiate differences in muscle utilization among subjects. CrCEST results were compared with (31)P MRS results showing good agreement in the Cr and PCr recovery kinetics. A relationship of 0.45 % CrCEST(asym)/mM Cr was observed across all subjects. CONCLUSION: Demonstrated the CrCEST technique could be applied at 3T to measure dynamic changes in creatine in in vivo muscle. The widespread availability and clinical applicability of 3T scanners has the potential to clinically advance this method.